The Portability of Ideas in Global Data Governance: A Coxian Reading of ‘Data Free Flow with Trust’ Journey to the UN Global Digital Compact - Dasnita, M. Nur Rahman; Sudirman, Arfin; Wibawa, Satriya (Yayasan Ilomata, 2026)
This article investigates the institutionalization of “trusted cross-border data flows” and “interoperability” within the UN Global Digital Compact. Employing a Coxian framework of ideas, material capabilities, and institutions, it argues this outcome was not passive diffusion. Instead, it was the product of a historic bloc that aligned U.S. policy with the interests of major technology firms. Through a directed content analysis of key diplomatic texts from the G20, OECD, and UN, the study traces the genealogical journey of this conceptual pairing. The analysis reveals how this highly portable formula was progressively embedded and proceduralized in the GDC's final text. The article also demonstrates that the success of this ideational project is underwritten by material power: the concentrated structure of global cloud infrastructure, which makes this governance settlement the most feasible option. The research illuminates how hegemonic consensus in digital governance is achieved through a mutually reinforcing alignment of adaptable ideas, strategic institutionalization, and the realities of material capabilities.